THE STRUGGLE OF TOURISM MANAGEMENT OF TANAH LOT CULTURAL HERITAGE IN BERABAN VILLAGE, TABANAN - Laksmi, A.A. Raka Sita; Ardika, I Wayan; Wirawan, A.A. Bagus; Mudana, I Gede (E-Journal of Cultural Studies; Vol 8 No 4 (2015): Volume 8, Number 4, November 2015, 2015)
The struggle of management of Tanah Lot tourism interest cultural heritage is a conflict among Tabanan government, CV Aryjasa Wisata, and Beraban people because of the unsatisfactory of the community toward the involvement of CV Aryjasa wisata. The problems in this research are (1) how is the dynamics of the struggle in managing tourism interest cultural heritage Tanah Lot, (2) what is the ideological background of the struggle in managing tourism interest of Tanah lot, and (3) what is the meaning of the struggle of management of Tanah Lot tourism interest. They are analyzed by applying theory of practice (Bourdieu), theory of power and knowledge (Foucault), and theory of communicative acts (Habermas). Data collection is conducted by technique of observation, interview, and documentation. The result of the research shows, firstly, the dynamics of the struggle is a historical continuity and discourse discontinuity started from the emergence of the idea in 1971 until 2011 which produced four systems of management which covered personal, contract, collaboration and partnership. The practical struggles includes system of management, position of operation manager, ownership of cultural heritage, and the struggle of power. The representation of the struggle’s result is in the form of management board construction and operation management. Secondly, the ideological background of the struggle covers capitalism, tourism, and tri hita karana . Thirdly, the meaning of the struggle covers; democratization strengthen, community empowerment, cultural heritage preservation, and the needs of the tourism industry image.
Keywords: struggle, management, tourism interest, cultural heritage, and ideology